Renewable and non-renewable energy consumption and economic activities: Further evidence from OECD countries - Salim, Ruhul; Hassan, K.; Shafiei, S. (Elsevier, 2014)
This article examines the dynamic relationship between renewable and non-renewable energy consumption and industrial output and GDP growth in OECD countries using data over the period of 1980–2011. The panel cointegration technique allowing structural breaks is used for empirical investigation. The results show that there is a long-term equilibrium relationship among non-renewable and renewable energy sources, industrial output and economic growth. The panel causality analyses show bidirectional causality between industrial output and both renewable and non-renewable energy consumption in the short and long run. However, there is evidence of bidirectional short-run relationship between GDP growth and non-renewable energy consumption while unidirectional causality between GDP growth and renewable energy consumption. These results indicate that OECD economies still remain energy-dependent for their industrial output as well as overall economic growth. However, expansion of renewable energy sources is a viable solution for addressing energy security and climate change issues, and gradually substituting renewable to non-renewable energy sources could enhance a sustainable energy economy.